X-Linked Agammaglobulinemia Presenting as Neutropenia: Case Report and an Overview of Literature - Lanlokun, Mosopefoluwa; Borden, Amanda; Nieves, Daime; Walter, Jolan E.; Albright, Deborah (Frontiers in Pediatrics, 2021)
X-linked agammaglobulinemia (XLA) is an inherited immunodeficiency caused by mutations in the Bruton Tyrosine Kinase (BTK) gene. Marked neutropenia can be the initial abnormal laboratory finding in patients with XLA who are presenting with their first illness. The two cases presented herein support early consideration of evaluation for primary humoral immune deficiency in previously healthy male patients under the age of 12 months who present with neutropenia in the setting of infection shortly after passively acquired maternal antibody has sufficiently waned. Initial consideration of XLA (or other humoral immune deficiencies) in this particular population of young male neutropenic patients may afford the opportunity to avoid bone marrow biopsy in otherwise stable cases with similar presentations.